Implementation of system methods of occupational hazard management - Бойченко, Николай Викторович (Technology audit and production reserves, 2014)
The need for implementing system methods in the management of occupational hazards is substantiated in the paper. A scientific and methodological approach to implementing the system methods of the occupational hazard management in the enterprise safety control system, based on the formalization of an occupational safety system, identification of ways and steps in implementing the system methods in the occupational hazard management was proposed. The need for scientific and practical developments in this area is justified by the development of labor protection approaches taking into account the international standards recommendations, in which conceptual ways of managing occupational hazards are given. A systematic approach to occupational hazard management is characterized by determining a goal based on the created policy, sequential actions to achieve the goals, checking the extent of their achievement. Implementing the systematic approach to reduce the threat of exposure to hazardous and harmful factors and to identify ways of their elimination on the basis of preventive measures will allow assessing, analyzing and improving the results of occupational hazard management. This can increase the level of work safety in the workplace.